5.8k views
3 votes
− 10x− 6y= 12
4x+ 7y=− 14

− 10x− 6y= 12 4x+ 7y=− 14-example-1

1 Answer

2 votes

Answer:

x = 0, y = -2

Explanation:


\left \{ {{-10x-6y=12} \atop {4x+7y=-14}} \right. = \left \{ {{-10x=12+6y} \atop {4x+7y=-14}} \right. = \left \{ {{x=(12+6y)/(-10) }(1) \atop {4x+7y=-14}} \right

Replace x from formula (1) to formula (2), we got:


4*(12+6x)/(-10)=-14 <=> (-2)/(5)(12+6y)+7y=-14 <=> (-24)/(5) + (-12)/(5)y+7y=-14 <=> (23)/(5)y = (-46)/(5) <=> y = -2\\=> x= (12+6*(-2))/(-10) = 0

User BradleyIW
by
5.2k points